Deskripsi Konseli pada Proses Konseling: Refleksi Al Qur’an Surah Asy Syams - Ibnu Ahmad, Karyono; Setiawan, Muhammad Andri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
This article aims to examine the description of counselee in the counseling process according to Surah Asy Syams, which is based on the author's reflection during counseling practice using the Qur'an media. Researchers found that counselees in the counseling process generally divided into three broad categories namely, (1) counselee based on growth and development level expressed based on sura Al Mukmin verse 67; (2) a special treatment counsel to women, referring to the Bukhari and Muslim narrated by Abu Hurairah Ra who calls women a crooked rib; and (3) the last counselor with special needs refers to Abasa 'verses 1-11. The counselee description in the counseling process based on the surah Asy Syams is divided into three parts: (1) the counselee has not understood the obstacles of his whole (sura Asy Shams verses 1-6); (2) the counselee when he finds out how to solve the obstacles he experienced (sura Asy Shams verses 7-10); and finally, the condition of the counselee who does not want to change the obstacles he experienced by analogizing the Thamud experienced (Surah Asy Syams verses 11 through 15)